Analisis Faktor-Faktor Yang Memengaruhi Keputusan Konsumen Terhadap Pembelian Minyak Goreng Kemasan Di Kecamatan Tuah Madani Kota Pekanbaru - Aludra, Sahla; Malik, Tamara Clarentine; Tety, Ermy; Hadi, Syaiful (Universitas Jambi, 2024)
People nowadays choose packaged cooking oil over bulk cooking oil. This phenomenon is due to the fact that people already think that packaged cooking oil is cleaner and more hygienic. Changes in people's lifestyles affect the demand for packaged cooking oil so that producers try to meet demand. The variety of packaged cooking oil in circulation makes people have their own preferences in determining which packaged cooking oil to use. Apart from being influenced by product attributes, consumer behavior factors also influence these preferences. This study aims to analyze the relationship between product attributes and purchasing decisions for packaged cooking oil and analyze the relationship between consumer behavior factors and purchasing decisions for packaged cooking oil in Tuah Madani District. This research was conducted in traditional markets and modern markets in Tuah Madani District. The sampling method used purposive sampling with the number of samples determined using the Slovin formula. The sample in this study were 110 respondents. The data analysis used in this study used the Spearman Rank correlation test analysis. The results of the analysis obtained the results, namely: (1) The relationship between product attributes and purchasing decisions for packaged cooking oil in Tuah Madani District is that there is a fairly strong, positive, and significant relationship. (2) The relationship between consumer behavior factors on purchasing decisions for packaged cooking oil.